A pyruvate decarboxylase-mediated therapeutic strategy for mimicking yeast metabolism in cancer cells. (September 2016) - Scott, Bronwyn; Shen, Jianliang; Nizzero, Sara; Boom, Kathryn; Persano, Stefano; Mi, Yu; Liu, Xuewu; Zhao, Yuliang; Blanco, Elvin; Shen, Haifa; Ferrari, Mauro; Wolfram, Joy
Graphical abstract: Abstract: Cancer cells have high rates of glycolysis and lactic acid fermentation in order to fuel accelerated rates of cell division (Warburg effect). Here, we present a strategy for merging cancer and yeast metabolism to remove pyruvate, a key intermediate of cancer cell metabolism, and produce the toxic compound acetaldehyde. This approach was achieved by administering the yeast enzyme pyruvate decarboxylase to triple negative breast cancer cells. To overcome the challenges of protein delivery, a nanoparticle-based system consisting of cationic lipids and porous silicon were employed to obtain efficient intracellular uptake. The results demonstrate that the enzyme therapy decreases cancer cell viability through production of acetaldehyde and reduction of lactic acid fermentation.